2011
DOI: 10.1002/ijc.25760
|View full text |Cite
|
Sign up to set email alerts
|

The NP9 protein encoded by the human endogenous retrovirus HERV‐K(HML‐2) negatively regulates gene activation of the Epstein‐Barr virus nuclear antigen 2 (EBNA2)

Abstract: Epstein-Barr virus (EBV) is a human tumour virus that efficiently growth-transforms primary human B-lymphocytes in vitro. The viral nuclear antigen 2 (EBNA2) is essential for immortalisation of B-cells and stimulates viral and cellular gene expression through interaction with DNA-bound transcription factors. Like its cellular homologue Notch, it associates with the DNA-bound repressor RBPJj (CSL/CBF1) thereby converting RBPJj into the active state. For instance, both EBNA2 and Notch activate the cellular HES1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…In addition, different HML-2 proviruses have different ORFs that dictate which retroviral proteins are expressed in vivo (7). Likewise, investigation into whether type 1 or type 2 proviruses are expressed differently during HIV-1 infection could elucidate new cellular functions for the accessory proteins Rec and Np9, as their expression is associated with malignancy (43,67,68).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different HML-2 proviruses have different ORFs that dictate which retroviral proteins are expressed in vivo (7). Likewise, investigation into whether type 1 or type 2 proviruses are expressed differently during HIV-1 infection could elucidate new cellular functions for the accessory proteins Rec and Np9, as their expression is associated with malignancy (43,67,68).…”
Section: Discussionmentioning
confidence: 99%
“…1). Since Tat has been shown to activate both viral and cellular genes (15,52,86,90,110), and since we observed that Jurkat-Tat cells have higher HERV-K (HML-2) gag RNA expression compared to the parental Jurkat counterpart, we hypothesized that the HIV-1 Tat protein might play a role in activating HERV-K (HML-2) expression during HIV-1 infection.…”
Section: Herv-k (Hml-2) Rna Expression Is Increased In Hiv-1-infectedmentioning
confidence: 99%
“…The HERV-K (HML-2) proteins Rec and Np9 provide a potential link between HERV-K (HML-2) and oncogenesis (4,6,18,31,41,52,67,101). Both proteins have been shown to stimulate c-Myc expression by binding and inhibiting the c-myc gene repressor promyelocytic leukemia zinc-finger protein (PLZF [31]), and Rec has also recently been shown to interact with the testicular zinc-finger protein, another transcriptional repressor (67).…”
mentioning
confidence: 99%
“…Their mechanism of regulation is suggested by the binding of EBNA2 with cellular transcription factors RBPJ, CBF-2/AUF1 or Spi-1/PU.1 to specific response elements of each promoter (137). Recent work has demonstrated that human endogenous retrovirus K nuclear protein NP9 can bind to EBNA2 and negatively regulate the EBNA2-mediated activation of the EBV viral C-and LMP2A promoters (88). The carboxy-terminal acidic activation domain of EBNA2 is required for direct interaction with the CSL family of DNA-binding protein (CBF1) and participates in EBNA2-mediated gene transcription (306).…”
Section: The Molecular Mechanisms Of Ebv Infection and The Effects Onmentioning
confidence: 99%